2015
DOI: 10.1002/2014jf003289
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate‐depth icequakes and harmonic tremor in an Alpine glacier (Glacier d'Argentière, France): Evidence for hydraulic fracturing?

Abstract: We detected several thousand deep englacial icequakes on Glacier d'Argentière (Mont‐Blanc massif) between 30 March and 3 May 2012. These events have been classified in eight clusters. Inside each cluster, the waveforms are similar for P waves and S waves, although the time delay between the P waves and the S waves vary by up to 0.03 s, indicating an extended source area. Although these events were recorded by a single accelerometer, they were roughly located using a polarization analysis. The deepest events we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 44 publications
(97 reference statements)
4
49
0
Order By: Relevance
“…Finally, simple models of hydraulic fracture resonance (Lipovsky and Dunham, 2015) and turbulent channel flow (Gimbert et al, 2014) predict spectral signatures that are not consistent with the evenly spaced spectral peaks observed on the WIP, although complex geometrical effects may invalidate the simplifying assumptions of such models. These distinguishing criteria may be useful in analyzing several recently described data sets (Heeszel et al, 2014;Helmstetter et al, 2015a, b;Hammer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, simple models of hydraulic fracture resonance (Lipovsky and Dunham, 2015) and turbulent channel flow (Gimbert et al, 2014) predict spectral signatures that are not consistent with the evenly spaced spectral peaks observed on the WIP, although complex geometrical effects may invalidate the simplifying assumptions of such models. These distinguishing criteria may be useful in analyzing several recently described data sets (Heeszel et al, 2014;Helmstetter et al, 2015a, b;Hammer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the authors' view, changing water pressures within englacial conduits displace the conduit walls causing nearly monochromatic wave trains recorded near Alaskan glaciers. The triggering water pressure change may be caused by nearby fracturing, and thus also explains near‐monochromatic coda, which is sometimes observed after deep icequakes [ West et al , ; Röösli et al , ; Helmstetter et al , ]. This phenomenon is again analogous to “hybrid events” in volcanic environments [ White et al , ; Neuberg et al , ; Harrington and Brodsky , ].…”
Section: Seismicity Related To Glacier Hydraulicsmentioning
confidence: 99%
“…Accordingly, the activity of intermediate icequakes in glacier ablation zones depends on the availability of meltwater. A study of 20–130 m deep icequakes on Glacier d'Argentière (France) showed sporadic bursts in the activity of intermediate icequake clusters [ Helmstetter et al , ]. The waveforms of these icequakes are also consistent with tensile faulting, and variations in depths of icequakes belonging to a single cluster coincided with the warmest periods.…”
Section: Seismicity Related To Glacier Hydraulicsmentioning
confidence: 99%
“…Lawrence and Qamar [] suggested that fluid‐filled fractures cause resonance effects in volcanoes and glaciers. Several subsequent studies have shown that water resonances triggered by fracturing in glacier ice are a common phenomenon in high melt areas [ Métaxian et al , ; West et al , ; Röösli et al , ] and that temporal changes in resonance peaks may reflect geometric changes associated with fracture tip propagation [ Heeszel et al , ; Helmstetter et al , ]. Considering recent advances in theoretical treatments of guided waves in englacial fractures [ Dunham and Ogden , ; Lipovsky and Dunham , ], these findings suggest that seismology is well suited to monitor subsurface water drainage in glaciers and ice sheets.…”
Section: Introductionmentioning
confidence: 99%